2004
DOI: 10.1016/j.cedpsych.2003.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of concept mapping on achievement, self-regulation, and self-efficacy in students of English as a second language

Abstract: This manuscript has been reproduced from the microfilm m aster. UMI films the text directly from the original or copy submitted. Thus, som e thesis and dissertation copies are in typewriter face, while others may be from any type of com puter printer.The quality of th is reproduction is dependent upon th e quality of th e c o p y subm itted. Broken or indistinct print colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignm ent can adversely affect rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
112
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(135 citation statements)
references
References 66 publications
9
112
0
4
Order By: Relevance
“…However, Chularut and DeBacker's (2004) comparison of learners at different proficiency levels revealed that there is no advantage for SBI in more advanced levels (see also Maxim, 2002). Despite the lack of control for proficiency level in primary studies, the meta-analysis of the current study allows for making comparisons between different levels of proficiency.…”
Section: Contextsmentioning
confidence: 99%
“…However, Chularut and DeBacker's (2004) comparison of learners at different proficiency levels revealed that there is no advantage for SBI in more advanced levels (see also Maxim, 2002). Despite the lack of control for proficiency level in primary studies, the meta-analysis of the current study allows for making comparisons between different levels of proficiency.…”
Section: Contextsmentioning
confidence: 99%
“…Among different vocabulary learning strategies, graphic organizers are highly recommended as they provide learners with visual scaffolds (Chularut & DeBacker, 2003). Word webbing is a kind of graphic organizer that according to Pierson, Cerutti, and Swab (2006) is appropriate for developing and reviewing vocabulary.…”
Section: Introductionmentioning
confidence: 99%
“…Chularut and DeBacker's (2004) study demonstrated that using concept mapping, a type of graphic organizers, students were able to comprehend reading passages more effectively than the study only counterparts. Of interest to the current study is that even with a 30 minute explicit lesson on the use of the concept map, students were able to show significant gains in reading comprehension of informational text over teacher led discussion.…”
Section: Pretest and Posttest Instruments Were The Test Of English Asmentioning
confidence: 97%
“…With ELL students, (a) teacher modeling of the map, the recursive process that the teacher and the students used to build and refine knowledge during the reading and (b) the actual use of the graphic organizer impacted positively on student learning. Chularut and DeBacker (2004) investigated the effectiveness of concept mapping as a learning strategy with ELL students on achievement, self-regulation, and selfefficacy versus individual study plus discussion group. For the purpose of this study, the results of the achievement of concept mapping with the use of graphic organizers is of interest.…”
Section: Pretest and Posttest Instruments Were The Test Of English Asmentioning
confidence: 99%
See 1 more Smart Citation